Even Square Semigroups - S. K. Pandey (International Journal of Mathematics And its Applications, 2017)
In this article we introduce the notion of even square semigroups and provide some examples. Even square semigroups have non-explicit appearances in the mathematical literatures and the idea to introduce them explicitly has emerged through authorтАЩs recent work on even square rings.